Modifikasi Pembobotan Systemic Important Score dengan Principal Component Analysis - Anwar, Samsul (Jurnal Ekonomi dan Pembangunan Indonesia, 2018)
The Financial Services Authority regulation No.46/POJK.03/2015 states that the calculation of Systemic Important Score (SIS) of a bank uses the same weighting for all three indicators: size, interconnectedness, and complexity. It disowns the possibility that one those indicators may give more contribution in determining the data structure of SIS assessment component than the others. This study offers an alternative weighting system to calculate SIS. The weighting system is based on eigenvectors of Principal Component Analysis by starting with standardizing the data. The simulation results show that the order of banking systemic levels in Indonesia from the highest are banking BUSN Devisa, Persero, Asing and BPD, Campuran, and BUSN Non Devisa.